PROSES PENYELESAIAN SENGKETA HAK TAS TANAH MELALUI MEDIASI DI KANTOR PERTANAHAN KOTA PADANGSIDIMPUAN - Marwan Busyro; Ridwan Rangkuti (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2020)
The purpose of this study is to find out how the process of resolving disputes over land rights through mediation and what are the obstacles to the process of resolving disputes over land rights through mediation at the Padangsidimpuan City Land Office. From the results of the research and discussion, it can be concluded that the procedures or procedures for resolving disputes conducted by the Land Office include stages (1) pre-mediation, (2) mediation. In resolving disputes over land rights at the Padangsidimpuan City Land Office, there are several obstacles, namely (1) the existence of obstacles from the disputing parties such as the absence of parties to fulfill the invitation to mediate (2) there is no good intention from each party (3) differences in ability and education among the parties (4) rules deemed to slow down the dispute resolution process (5) complainants often do not know the requirements and procedures for dispute resolution at the Padangsidimpuan City Land Office.Keywords: Process of Dispute Resolution, Mediation, Land Office.